2012
DOI: 10.4321/s1695-61412012000300006
|View full text |Cite
|
Sign up to set email alerts
|

Prejuicios de las enfermeras hacia la población inmigrante: una mirada desde el Sur de España

Abstract: Extract.In the last decades Spain has turned into a receiver of immigrants, this increase has lead to a growing cultural diversity in society which is reflected in the change of the cultural profile of the people who use the public health system.In this project our aim is to approach and understand the prejudices of the nursing staff towards the immigrant population. Methodology.Transversal Quantitative Study. Participants: Nursing professionals from the three public hospitals of Almería. Data collection: Anon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…Regarding the healthcare entitlement of the immigrant population, significant differences were observed in responses to the items "the collapse of the health system is largely due to increased immigration" and "in the medium term, the mass arrival of immigrants will cause major healthcare and social problems", where for both items students in Toledo had a worse attitude, followed by Melilla and Coimbra, in that order. These data match those obtained from a sample of nurses in a district hospital in Melilla [19] and from other hospitals in Spain, where the immigrant population is considered to be a major consumer of healthcare resources [39][40][41][42][43]. The fact that students in Melilla have a worse attitude as regards the immigrant population's healthcare rights may be explained by the fact that there is only one hospital in this city, which delivers healthcare not only to the city's residents but also to thousands of Moroccans who cross the border every day specifically to be treated in this hospital [44].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Regarding the healthcare entitlement of the immigrant population, significant differences were observed in responses to the items "the collapse of the health system is largely due to increased immigration" and "in the medium term, the mass arrival of immigrants will cause major healthcare and social problems", where for both items students in Toledo had a worse attitude, followed by Melilla and Coimbra, in that order. These data match those obtained from a sample of nurses in a district hospital in Melilla [19] and from other hospitals in Spain, where the immigrant population is considered to be a major consumer of healthcare resources [39][40][41][42][43]. The fact that students in Melilla have a worse attitude as regards the immigrant population's healthcare rights may be explained by the fact that there is only one hospital in this city, which delivers healthcare not only to the city's residents but also to thousands of Moroccans who cross the border every day specifically to be treated in this hospital [44].…”
Section: Discussionsupporting
confidence: 52%
“…Other items that may reflect this anti-immigrant feeling are those relating to loss of identity or increased crime rates, for example "immigrants who commit a crime should be deported" and "the arrival of immigrants has led to increased crime", with the least favorable attitude being held by students in Coimbra, followed by students in Melilla and then students in Toledo; other studies revealed similar data [10,[36][37][38][39].…”
Section: Discussionmentioning
confidence: 93%